Perbedaan Nilai Fevr Pada Laki-Laki Antara Pekerja Kantoran Dan Pekerja Yang Terpapar Polusi - Azizah, Umi Nur; , dr. Sri Wahyu Basuki, M.Kes; , dr. Dodik Nursanto (2015)
Background : FEVR is one of pulmonary function examination. Normal value of FEVR is ≥ 80%. The lower value of FEVR indicate an increasing of respiratory disorder and systemic inflammatory. Low value of FEVR affected by some factors such as air pollution. Air pollutant has a big role to affect the lungs which leads to inflammation of respiratory tract. Objective : This study aims to found the difference between the FEVR in men between Officer and pollutant exposed workers. Methods : This research used analytic observational research design with cross sectional approach. Samples are divided into two groups, officer and pollutant exposed workers. Each group consist of 30 respondents in 20-59 years old. The sampling technique using purposive sampling and continued with a Mann-Whitney test. Results : The mean value of FEVR in this research shows that the FEVR value is higher on officer (97,5357%) compared to pollutant exposed workers (93,3698 %). Mann-Whitney test results, obtained the value of Sig 0,004 (P = 0.004), because the value of P < 0.05 " there is significant differences statistically ". Conclusion : There is a difference between the value of FEVR in men between officer and pollutant exposed workers.